2016
DOI: 10.1001/jamasurg.2015.3414
|View full text |Cite
|
Sign up to set email alerts
|

Self-harm Emergencies After Bariatric Surgery

Abstract: In this study, the risk of self-harm emergencies increased after bariatric surgery, underscoring the need for screening for suicide risk during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(89 citation statements)
references
References 60 publications
4
79
0
6
Order By: Relevance
“…Nonetheless, regardless of the type of surgery our patients undergo, there is an increasing appreciation of the cumulative effect of psychiatric disorders that influence long-term outcomes. 5 In this issue of JAMA Surgery, Bhatti and colleagues 6 present an intriguing self-matched longitudinal study assessing the risk of self-harm emergencies in patients who have undergone bariatric surgery. The study has excellent follow-up, with all patients having 3 years of preoperative and postoperative data.…”
mentioning
confidence: 99%
“…Nonetheless, regardless of the type of surgery our patients undergo, there is an increasing appreciation of the cumulative effect of psychiatric disorders that influence long-term outcomes. 5 In this issue of JAMA Surgery, Bhatti and colleagues 6 present an intriguing self-matched longitudinal study assessing the risk of self-harm emergencies in patients who have undergone bariatric surgery. The study has excellent follow-up, with all patients having 3 years of preoperative and postoperative data.…”
mentioning
confidence: 99%
“…The authors reported an increase in self-harm diagnosis from 0.38 per 100 person-years before to 0.59 per 100 person-years two years after surgery. Supporting the discovery of increased self-harm behavior, a Canadian research group led by Bhatti et al (2016) examined changes in self-harm emergencies after bariatric surgery in a sample of 8,815 adult patients, with a followup for each patient from three years prior to surgery to three years after surgery. Self-harm events rose from 2.33 events per 1000 patients annually pre-surgery to 3.63 events per 1000 patients annually in the postoperative period.…”
Section: Self-harm and Suicidalitymentioning
confidence: 99%
“…Moreover, the suicide rate increases after surgery in patients, particularly in females more than 35 years of age. Hence, preoperative psychiatric analysis of patients in this population is extremely important (19). The antidiabetic benefits of surgery often wane over time.…”
Section: Ignored Issues For Bariatric Surgery In the Present Studiesmentioning
confidence: 99%